2012
DOI: 10.4074/s1966960712004043
|View full text |Cite
|
Sign up to set email alerts
|

Demande de séjour touristique en espace rural et vecteurs de valorisation marchande d’aménités naturelles et patrimoniales 1

Abstract: -L'analyse empirique de la demande touristique dans les espaces ruraux reste encore très peu abordée dans la littérature en économie du tourisme. Dans cette étude, la méthode des expériences de choix discrets a été adaptée pour analyser les préférences pour différents types de séjours de courte durée, dans les territoires de l'estuaire de la Gironde. Les résultats d'une enquête en ligne menée en 2011 a permis de constater que les individus préfèrent les séjours de nature. Ils sont prêts à payer ceux-ci aussi c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Indeed, creating such variables for spread attractions would have required examining each attraction on a case-bycase basis, which is not compatible with a study based on national data. As many studies have shown the positive effect of natural amenities (Marcouiller, Kim and Deller, 2004;Rambonilaza, 2012) and as these attractions are very often wide attractions, this point remains an important issue. Thus, future research conducted on a more limited scale could allow for the measurement of the spatial extent of the influence of spread attractions.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, creating such variables for spread attractions would have required examining each attraction on a case-bycase basis, which is not compatible with a study based on national data. As many studies have shown the positive effect of natural amenities (Marcouiller, Kim and Deller, 2004;Rambonilaza, 2012) and as these attractions are very often wide attractions, this point remains an important issue. Thus, future research conducted on a more limited scale could allow for the measurement of the spatial extent of the influence of spread attractions.…”
Section: Discussionmentioning
confidence: 99%
“…A couple of papers used several methods or elicitation questions. For instance, Dachary-Bernard and Rambonilaza ([2012]) employed both CE and the CV methods to value a landscape (Monts d'Arrée). Figure 1 shows that the number of publications tends to increase in the long run, although there are variations in the short run.…”
Section: Construction Of the Database For Francementioning
confidence: 99%